2018
DOI: 10.1039/c8ra04421j
|View full text |Cite
|
Sign up to set email alerts
|

SnS/C nanocomposites for high-performance sodium ion battery anodes

Abstract: Sodium-ion batteries have been considered as one of the most promising types of batteries, beyond lithium-ion batteries, for large-scale energy storage applications. However, their deployment hinges on the development of new anode materials, since it has been shown that many important anode materials employed in lithium ion batteries, such as graphite and silicon, are inadequate for sodium-ion batteries.We have simply prepared novel SnS/C nanocomposites through a top-down approach as anode materials for sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Grand potential diagrams as a function of the chemical potential of K were obtained to investigate the reaction potential and theoretical capacity of the anode materials. Metal/metalloid anodes and binary metal compounds, including the anions P, O, and S that were reported as promising anode materials for LIBs and SIBs, were thoroughly explored in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Grand potential diagrams as a function of the chemical potential of K were obtained to investigate the reaction potential and theoretical capacity of the anode materials. Metal/metalloid anodes and binary metal compounds, including the anions P, O, and S that were reported as promising anode materials for LIBs and SIBs, were thoroughly explored in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Templated hybrid nanostructures, such as flexible films of CNT/AuNW hybrid structures, are used in supercapacitors, which increase the stability and power density (low contact resistance) many times thanks to nanotubes [ 225 ]. Additionally, work [ 226 ] has shown that flexible energy storage devices could be based on nanocomposite paper. Nanoporous cellulose paper embedded with aligned carbon nanotube electrode and electrolyte constitutes the basic unit.…”
Section: Resultsmentioning
confidence: 99%
“…As the battery is discharged to 0.70 V, monoclinic Na 4 Sn 3 S 8 (PDF #29-1277), tetragonal Sn (PDF #04-0673), and SnÀ Na alloy (namely: Na z Sn, z > x + y) are detected. [26,38,39] When the battery is discharged to 0.4 V, the peak intensity of Na z Sn gets stronger, while the peak intensity of Na 4 Sn 3 S 8 /Sn tends to be weaker, suggesting a phase transition from Na 4 Sn 3 S 8 /Sn to Na z Sn. With the discharging process further decreased to 5 mV, the XRD peak of Na 4 Sn 3 S 8 disappears, implying that all the Na 4 Sn 3 S 8 is completely converted into Na 2 S and Na z Sn.…”
Section: Resultsmentioning
confidence: 99%